Factors affecting research utilisation of nurses and midwives working in North Gondar and West Gojjam Zone public hospitals, Ethiopia: a cross-sectional study - Dagne, Asrat Hailu (BMJ Open, 2020)
BACKGROUND: Research utilisation in clinical decision-making is crucial to enhance quality healthcare, professional development and cost-effective health service. Nurses and midwives have a vital role in research utilisation. However, many factors influence research utilisation of nurses and midwives. OBJECTIVES: To determine research utilisation and identify factors that affect research utilisation among nurses and midwives. METHODS: An institutional-based, cross-sectional study was conducted from 23 May to 30 June 2019. A total of 631 nurses and midwives participated in the study. Categorical variables were coded with dummy variables and multiple linear regression model was carried out. The level of significance was set at p value less than or equal to 0.05 with 95% CI. RESULTS: Participants’ total mean score in the research utilisation scale was 2.27 (SD±0.77) and their mean age was 28.41 (SD±4.71) years. The study revealed that 70.4% (444) of participants had poor research utilisation. Self-efficacy in research utilisation skills (B=0.86, 95% CI 0.75 to 0.97), support for research utilisation (B=0.4, 95% CI 0.25 to 0.55), attitude (B=0.23, 95% CI 0.07 to 0.38), barriers to research utilisation (B=−0.63, 95% CI −0.72 to −0.54), nursing/midwifery work index (B=0.07, 95% CI 0.04 to 0.11) and hospital’s level of healthcare (B=4.5, 95% CI 2.13 to 6.9) were statistically significantly associated factors of research utilisation. CONCLUSIONS: This study revealed poor research utilisation among nurses and midwives. Barriers to research utilisation, supporting factors for research utilisation, attitude, self-efficacy in research utilisation skills, hospital’s level of healthcare and nursing/midwifery work index were found to be statistically significant predictors of research utilisation. The most common barriers to research utilisation were insufficient time and inability to understand statistical terms used in research articles.